2012
DOI: 10.1002/mrm.24591
|View full text |Cite
|
Sign up to set email alerts
|

Spin echo measurements of the extravasation and tumor cell uptake of hyperpolarized [1‐13C]lactate and [1‐13C]pyruvate

Abstract: Purpose: To assess the blood-tissue distribution of hyperpolarized 13 C-labeled molecules in vivo. Methods: Spin-echo experiments with simultaneous acquisition of the free induction decay (FID) signal following the excitation pulse and the spin-echo signal, were used to monitor hyperpolarized [1- 13C]lactate, [1-13 C]pyruvate, and the perfusion marker, [13 C]HP001, following their intravenous injection into tumor-bearing mice. Apparent T 2 relaxation times and diffusion coefficients were also measured. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 37 publications
10
80
2
Order By: Relevance
“…It has been suggested that MCTs are rate limiting in T47D breast cancer cells (17); this was investigated more quantitatively in EL-4 lymphoma cells (18), where it was found that the control of the measured rate of isotope flux is shared between both MCTs and LDH. The importance of MCTs in the apparent LDH rate constants measured by hyperpolarized 13 C NMR has been highlighted recently (19). Such deregulation of metabolic characteristics and the consequential change to apparent rate constants present potential biomarkers for therapeutic targets, and both the 1 H and 13 C NMR assays are sensitive to modulations of these important factors in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that MCTs are rate limiting in T47D breast cancer cells (17); this was investigated more quantitatively in EL-4 lymphoma cells (18), where it was found that the control of the measured rate of isotope flux is shared between both MCTs and LDH. The importance of MCTs in the apparent LDH rate constants measured by hyperpolarized 13 C NMR has been highlighted recently (19). Such deregulation of metabolic characteristics and the consequential change to apparent rate constants present potential biomarkers for therapeutic targets, and both the 1 H and 13 C NMR assays are sensitive to modulations of these important factors in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…2e). The decay curves were first fitted using the non-negative least squares (NNLS) method (10) and two T 2 * components were consistently observed for both [1][2][3][4][5][6][7][8][9][10][11][12][13] C] pyruvate and [1][2][3][4][5][6][7][8][9][10][11][12][13] C] lactate from most of the dynamic spectra. Based on this result, decay curves were fitted using a nonlinear curve fitting algorithm (11) with the following dual exponential signal model with DC bias A:…”
Section: Discussionmentioning
confidence: 99%
“…Following injection of hyperpolarized [1][2][3][4][5][6][7][8][9][10][11][12][13] C] pyruvate, increased [1-13 C] lactate signal was observed by rapid exchange of 13 C labeling between pyruvate and lactate (3) due to the high glycolytic rate of tumor characteristics (4). Intravenously injected [1-13 C] pyruvate is assumed to be predominantly in the intravascular space while the lactate is presumed to be largely in the intracellular space where the label exchange in the reaction catalyzed by the enzyme lactate dehydrogenase occurs (5). And a very rapid interconversion between lactate and pyruvate in blood has also been reported (6).…”
Section: C-labeled Metabolites In Vivo (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, small but noticeable differences in signal can be observed between SPEN and CSI, especially for pyruvate. These differences could be due to the additional diffusion weighting of the SPEN sequence, which is based on a spin echo [33]. Such weighting can decrease significantly the signal from the vasculature, the suppression of which is usually desirable as it can interfere with the measurement of metabolism.…”
Section: Measurements With 13 C Hyperpolarized Pyruvate In Ratsmentioning
confidence: 99%